Application of Enterprise Architecture in Digital Transformation of Insurance Companies - Prawira, Khairul Thamrin; Hindarto, Djarot; Indrajit, Eko (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Implementation of enterprise architecture is a major requirement for companies that want to develop business processes according to their needs. Business architecture is the company's initial plan to support the company's operations. An insurance company is a company that provides insurance services. Insurance is a form of contract in which the guaranteed party pays a premium to the insurance company. Insurance companies provide payment guarantees in the event of certain risks that are guaranteed in the insurance contract. Therefore, this company must think about operational forms to provide the best service for its customers. Structuring business processes starting from the sales process, administrative processes, claims processes, to financial processes which are the most vital processes. Insurance companies are different from other financial services companies, such as banking companies, fintech companies and others. The insurance company's unique process is to provide guarantees to its customers in carrying out risk protection. Before starting to implement enterprise architecture, the company already has a business architecture blueprint which is the enterprise architecture of a company. The design begins with running architectural business processes, architectural applications, architectural databases and architectural technology. Enterprise architecture implementation certainly cannot be separated from project management. Because project management is a process that manages the project so that the project becomes more organized in its implementation